CORRUPTION AND POLICY MAKING IN NIGERIA: STRENTHENING JUDICIAL INTEGRITY AND CAPACITY - Dantani, Umar; Shehu, Samaila (IJRDO - Journal of Social Science and Humanities Research, 2018)
This paper examined Corruption and Policy Making in Nigeria: Strengthening Judicial Integrity and Capacity. The method of data collection and framework of analysis are based on documentary analysis and underdevelopment theory. The paper argues that corruption is caused by poor leadership; lack of accountability, transparency and good governance; the monopoly of power by government officials; and the discretionary powers of politicians and bureaucrats over the formulation and interpretation of the rules and regulations and allocations of projects. The paper argues that corruption has seriously contributed to the underdevelopment in Nigeria because it drains the available resources for productive purposes and discourages investment. It also hinders Nigerian state to discharge its distributive function. In addition, corruption drails democracy and generates political violence. Furthermore, it intensifies abject poverty, conditions infrastructural decay and a general decline in the living standard of the citizenry. The paper argues that judiciary that is shouldered with responsibilities for punishing corrupt officials is confronted with institutional weaknesses, appointment of corruptible judicial officials, procedural deficiencies and absence of incorporation of information technology in the judiciary. The manifestations of these problems call for strengthening policy making through judicial integrity and capacity. This could be achieved through judicial independence and autonomy; appointment of judicial officials from retired judicial officials based on integrity, credibility and intellectual capacity; setting up time limit for ruling criminal and civil cases; upgrading ICT facilities for easy communication and administration of judicial proceedings. The paper concludes that if these measures are strengthened as policy levers corruption would be reduced to the bearest minimum.